Effects of salinity stress (NaCl) on growth attributes and some nutrient accumulation in cowpea (Vigna unguiculata) - Kouam, Eric Bertrand; Marie Solange Mandou, Ebeny Leonny Tsague (Current Botany, 2017)
This study investigates the impact of salinity (NaCl) on growth and ions accumulation in the leaves of three cowpea genotypes: OU100 and KEB-CP118 from Cameroon and ICV12 from Kenya. Four levels of salinity were used (0mM, 50mM, 100mM and 150mM) and the experiment was carried out in the greenhouse. Growth parameters were measured on 8 weeks old plants. Leaf ions concentrations (Na+, K+, K+/Na+) were determined. Â It was observed that increasing salinity induced significant increase in Na+ and substantial reduction in the accumulation of K+ in the leave of all genotypes. Pearsonâ€™s correlation analysis revealed significant association among most of the growth parameters. Water content in shoots was not affected by salinity for all genotypes; however salinity induced a reduction of water content in the root for ICV12 and OU100 genotypes. Generally, results highlighted that high salt concentrations significantly delayed the growth process. The delay was more pronounced for OU100 genotype. Therefore, genotype effect toward salinity tolerance was noticed. KEB-CP118 was the most tolerant genotype as salinity did not affect negatively growth parameters. Its remarkable behavior under salinity indicates it should be explored in selection programs, used in development of tolerant varieties and promoted for cultivation in tropical zones affected by salinity.